2010
DOI: 10.1590/s0104-77602010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nondestructive testing of laminations on the bending properties of glulam beams made from louro-vermelho (Sextonia rubra)

Abstract: This work aims to assess the bending properties of glued laminated timber beams (glulam) manufactured with species louro-vermelho (Sextonia rubra). Laminations were nondestructively tested using the transverse vibration method (E Mlam ). Then 10 glulam beams were manufactured and tested in static bending according to ASTM D 198 standard, having modulus of elasticity (E M ), modulus of rupture (f M ), and bending moment (M) determined. The finished beams were also tested by the transverse vibration method (E Mv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…On the other hand, the values of dynamic modulus of elasticity observed for boards were higher compared to veneers. [12], who employed the transverse vibration nondestructive method to grade lumber to produce glulam beams. The mechanical properties of the LVL boards are presented on Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the values of dynamic modulus of elasticity observed for boards were higher compared to veneers. [12], who employed the transverse vibration nondestructive method to grade lumber to produce glulam beams. The mechanical properties of the LVL boards are presented on Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Visual and acoustic nondestructive methods have been used previously to sort logs, lumber and veneers employed in the manufacturing of ply-based wood composites, as seen in several works [10][11][12][13][14][15]. Wang et al [15], while studying ultrasonically (US) rated veneer from red maple, found a positive relationship between veneer US variables and LVL billet stiffness and strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of assembling glulam beam from the well-known Brazilian Amazonian hardwood louro-vermelho (Sextonia rubra) was demonstrated in our previous study (Teles et al 2010). According to the results, the glulam beam presented the following flexural properties: modulus of elasticity, :15800 N/mm 2 ; modulus of rupture, :64 N/mm 2 ; and rupture load, :14600 N. Louro-vermelho is widely used in light construction and often found in the Northern states of Brazil.…”
Section: Introductionmentioning
confidence: 94%
“…After load reached 4000 N, the deflection measurement device was removed and the beam tested up to rupture. Further details on glulam beams assembling and testing can be found in Teles et al (2010).…”
Section: Theoretical and Experimental Deflection Evaluationmentioning
confidence: 99%